Delivering entrepreneurship education in Africa : new perspectives - Shambare, Richard; Iwu, Chux Gervase (Emerald Publishing Limited, 2023)
Entrepreneurship education is crucial for economic development. However, its current focus on Western pedagogy raises concerns about its relevance in Africa. The lack of African-oriented definitions of entrepreneurship education may be connected to the limited interest in entrepreneurship as a career in the region. Unlike developed countries, where entrepreneurship drives innovative industries, African entrepreneurship is often driven by survivalist intentions. This raises questions about how entrepreneurship in Africa contributes to the economy without promoting creative innovation. Given these factors, evaluating the role of entrepreneurship education in this context is essential. Delivering Entrepreneurship Education in Africa brings together a collection of academic studies that offer an in-depth analysis of the current state of entrepreneurship education in Africa. The chapter authors engage discussions on how to make entrepreneurship education an attractive field of study for African students. The chapters critique the current teaching styles of entrepreneurship and suggests creative ways of improving entrepreneurship pedagogy while offering approaches to make it an attractive field of study. Delivering Entrepreneurship Education in Africa appeals to academics, teachers, researchers, policymakers, planners, curriculum designers and entrepreneurs.